Analysis Of the Zakat Management System at The Amil Zakat Institution of Banarjoyo Village Batanghari Sub-District, East Lampung - Kurnia Abmilentri, Erba; Hakim Habibie, M. Luqmanul (Journal of Contemporary Applied Islamic Philanthropy, 2023)
Purpose: Zakat is one of the foundation instruments of the teachings of Islam. Zakat contributes greatly to the economic development of Muslims, as a very important part because it can improve the economy of the people. Amil Zakat Institution of Banarjoyo village is an amil institution in the Batanghari sub-district, East Lampung Regency, which is expected to be part of the social problem solver of the community. This study aims to determine the zakat management system in the form of zakat collection analysis, transparency, and accountability analysis. Methodology: This research methodology uses qualitative methodology by using a descriptive approach. This research includes field research. Data collection techniques in this research are interviews and documentation. Findings: Based on the research shows that the zakat collection system in Banarjoyo Batanghari village is carried out by distributing pamphlets, brochures, direct presentations to muzakki, print, and social media coverage. while the collection of zakat is carried out directly (coming) to the secretariat of the Amil Zakat Institution of Banarjoyo village, Batanghari District, East Lampung Regency.